Using swim‐up traps to assess Arctic charr (Salvelinus alpinus) spawning habitat and the phenology and density of emergent fry - Smith, Antony; Milner, Nigel; Papadopoulos, Alexander; Seymour, Mathew; Carvahlo, Gary (Fisheries management and ecology, 2024)
The Arctic charr (Salvelinus alpinus) is a species of cultural, economic and conservation importance, but hitherto, investigations of critical early life stages have been few. Here, at a lake in the United Kingdom, we used swim‐up traps to investigate the phenology of fry emergence and associations between fry density and habitat. The first emergence occurred on 4 or 5 March 2020 and 2021, with numbers peaking and remaining stable in the following 2 weeks. Emergence in 2021 had finished by 27 March but on the same date in 2020 emergence was ongoing when COVID‐19 ended sampling. Substrate particle size ranged 31–94 mm and was negatively correlated with fry density. Likewise, density was negatively correlated with water depth and aquatic plant cover, but there was no relationship with flow velocity. Traps were effective and non‐destructive for assessing the location and productivity of spawning sites for this locally threatened species.